Possibilities and realities of rehabilitation in cancer patients - A. G. Solopova; Y. Y. Tabakman; A. V. Vorobev; L. E. Vorobev (Акушерство, гинекология и репродукция, 2016)
Development of methods of combined, radiation and medication therapy of malignant tumors has improved the results of survival, background of what is becoming a very important task of medical and social rehabilitation of patients. Considering psychosomatic features of cancer patients, in the framework of the rehabilitation of such patients should be performed overall patient-oriented medical work, one of the essential parts of which are individual and group psychotherapy. An important aspect of rehabilitation of cancer patients in reproductive age is the preservation or restoration of reproductive and sexual function after treatment of the underlying disease. Separately, in a program of rehabilitation of cancer patients is the question of palliative care for incurable cancer patients.